Modelo para la Localización de un Plataforma de Cross Docking en el Contexto de Logística Focalizada - Kalenatic, Dusko; López Bello, César Amilcar; González Rodríguez, Leonardo José; Rueda Velasco, Feizar Javier (Ingeniería, 2007)
The current context of global defence scenarios has enhanced development of new concepts like focused logistics concept. Focused logistics is a concept created to support logistics operations in uncertainty environments. In this framework focused logistics needs tools to enable an agile, reliable and accurate decision processes. In order of these requirements, this paper shows a mathematical model as a support tool to find a good location of a cross-docking facility and allocate workloads of different kinds of vehicles from suppliers to demand centres being especially innovative to the strategy used for the solution of the present model.